2019
DOI: 10.1002/ijc.32025
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and secondary epidermal growth factor receptor (EGFR) T790M mutation among first‐line gefitinib, erlotinib and afatinib‐treated non‐small cell lung cancer patients with activating EGFR mutations

Abstract: Gefitinib, erlotinib and afatinib are approved for first‐line treatment of advanced non‐small cell lung cancer (NSCLC) bearing an activating epidermal growth factor receptor (EGFR) mutation. However, the clinical outcomes among the three EGFR tyrosine kinase inhibitors (TKIs) are still controversial. We aimed to evaluate clinical outcomes and secondary EGFR T790M mutation among the three EGFR TKIs. From May 2014 to January 2016, a total of 301 patients received treatment with gefitinib, erlotinib or afatinib, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
79
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 44 publications
(105 reference statements)
7
79
1
Order By: Relevance
“…Our study also identified that patients with common baseline EGFR mutations of Del-19 and L858R had a higher T790M acquisition rate compared to those with uncommon baseline EGFR mutations. Lin et al also reported that uncommon EGFR mutation had less secondary T790M acquisition (adjusted OR 0.14, 95% CI, 0.02–0.97; p = 0.047) compared with del-19 of EGFR mutation ( 18 ). In addition, the previous studies showed T790M was more frequent in patients with Del-19 compared to those with L858R ( 15 , 17 , 26 28 ), which was also observed as a trend but without statistical significance in our study.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Our study also identified that patients with common baseline EGFR mutations of Del-19 and L858R had a higher T790M acquisition rate compared to those with uncommon baseline EGFR mutations. Lin et al also reported that uncommon EGFR mutation had less secondary T790M acquisition (adjusted OR 0.14, 95% CI, 0.02–0.97; p = 0.047) compared with del-19 of EGFR mutation ( 18 ). In addition, the previous studies showed T790M was more frequent in patients with Del-19 compared to those with L858R ( 15 , 17 , 26 28 ), which was also observed as a trend but without statistical significance in our study.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, there were more erlotinib-treated (N = 154) and afatinib-treated patients (N = 91) in the present study. Lin et al enrolled 16 erlotinib-treated and 36 afatinib-treated patients (18). Huang et al enrolled 13 afatinib-treated patients (15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A population-based study involving 15 medical institutes that cover a population of three million people indicated the disadvantages of pre-treatment before AFA in patients with NSCLC harboring an acquired EGFR T790M mutation [18]. However, the evidence-based trials regarding the optimal regimen in the management of cases with T790M-positive NSCLC and multiple CNS metastases remain controversial [23,26]. Within this context, evidence has indicated that neither the firstgeneration nor second-generation EGFR-TKIs distinctly improve the OS among those cases with T790M-positive NSCLC [23,27].…”
Section: Discussionmentioning
confidence: 99%